2021
DOI: 10.3389/fendo.2021.763138
|View full text |Cite
|
Sign up to set email alerts
|

Oral Antidiabetics and Sleep Among Type 2 Diabetes Patients: Data From the UK Biobank

Abstract: Previous small-scale studies have found that oral antidiabetic therapy is associated with sleep difficulties among patients with type 2 diabetes (T2D). Here, we used data from 11 806 T2D patients from the UK Biobank baseline investigation to examine the association of oral antidiabetic therapy with self-reported difficulty falling and staying asleep and daily sleep duration. As shown by logistic regression adjusted for, e.g., age, T2D duration, and HbA1c, patients on non-metformin therapy (N=815; 86% were trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 32 publications
(41 reference statements)
0
5
0
Order By: Relevance
“…About type 2 diabetes, a study on 387 outpatients found that patients treated with metformin slept for approximately 36 min longer and exhibited a 6.4% higher sleep efficiency compared with other treatments (28). Consistently, a cross-sectional study on 11,806 diabetic patients showed that those treated with non-metformin drugs were more likely to report difficulty falling and staying asleep at night compared with those on metformin monotherapy (31). Our results are consistent with these observations.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…About type 2 diabetes, a study on 387 outpatients found that patients treated with metformin slept for approximately 36 min longer and exhibited a 6.4% higher sleep efficiency compared with other treatments (28). Consistently, a cross-sectional study on 11,806 diabetic patients showed that those treated with non-metformin drugs were more likely to report difficulty falling and staying asleep at night compared with those on metformin monotherapy (31). Our results are consistent with these observations.…”
Section: Discussionsupporting
confidence: 89%
“…Previous studies have supported a protective association between sleep and metformin in people with type 2 diabetes or polycystic ovarian syndrome (29)(30)(31). About type 2 diabetes, a study on 387 outpatients found that patients treated with metformin slept for approximately 36 min longer and exhibited a 6.4% higher sleep efficiency compared with other treatments (28).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…If GABA compensates for hypoinsulinemia during postprandial conditions in pediatric patients with hypopnea or periodic breathing, GABA could play a useful remedial role. This set of new information would be useful for studying the interactions of antidiabetic drugs and sleep, as discussed by others [ 13 ].…”
Section: Discussionmentioning
confidence: 98%
“…Maintaining insulin levels via GABA effects is more challenging for patients with OSA, because GABA influences insulin secretion under IH conditions induced by OSA, which could be unsafe; GABA also plays sedative roles that may further compromise breathing. Furthermore, a recent study on large samples of adult patients reported a higher odds ratio of up to 24% of sleep disturbance amongst patients taking non-metformin in comparison with those without antidiabetics [ 13 ], raising concerns of GABA’s effects on state transitions to sleep.…”
Section: Introductionmentioning
confidence: 99%